2010
DOI: 10.1016/s1473-3099(10)70202-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of artemether–lumefantrine compared with quinine in pregnant women with uncomplicated Plasmodium falciparum malaria: an open-label, randomised, non-inferiority trial

Abstract: Efficacy and safety of artemether-lumefantrine compared with quinine in pregnant women with uncomplicated Plasmodium falciparum malaria: an open-label, randomised, non-inferiority trial MSF Field Research SummaryBackground Malaria in pregnancy is associated with maternal and fetal morbidity and mortality. In 2006, WHO recommended use of artemisinin-based combination treatments during the second or third trimesters, but data on effi cacy and safety in Africa were scarce. We aimed to assess whether artemether-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
168
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(171 citation statements)
references
References 29 publications
3
168
0
Order By: Relevance
“…It is currently available at a subsidized cost in most countries where malaria is endemic. AL has proved to be not inferior to quinine in East Africa for the treatment of P. falciparum infection in the second and third trimesters of pregnancy (4). ACTs are recommended by the World Health Organization (WHO) as the first-line treatment for uncomplicated malaria in the second and third trimesters of pregnancy (5).…”
mentioning
confidence: 99%
“…It is currently available at a subsidized cost in most countries where malaria is endemic. AL has proved to be not inferior to quinine in East Africa for the treatment of P. falciparum infection in the second and third trimesters of pregnancy (4). ACTs are recommended by the World Health Organization (WHO) as the first-line treatment for uncomplicated malaria in the second and third trimesters of pregnancy (5).…”
mentioning
confidence: 99%
“…12 The protocols for these studies were approved by the Faculty Research Ethics Committee and the Institutional Review Board of the Mbarara University of Science and Technology (Mbarara, Uganda), and the Ugandan National Council for Science and Technology (Kampala, Uganda). The MIP study protocol was also approved by the Comité de Protection des Personnes (Ile-de-France XI, Paris, France).…”
mentioning
confidence: 99%
“…However, a recent study comparing the safety of ACT and quinine found no difference in adverse pregnancy outcomes when used in the second and third trimester [49].…”
Section: Future Challenge -Malaria In Pregnancymentioning
confidence: 97%